2004
DOI: 10.1071/sb03016
|View full text |Cite
|
Sign up to set email alerts
|

Application of RAPD and ISSR markers to analyse molecular relationships in Grevillea (Proteaceae)

Abstract: The potential of RAPD and ISSR markers to construct molecular relationships of Grevillea was evaluated with 23 RAPD and 12 ISSR primers. The 16 genotypes representing 12 species and 3 subspecies of Grevillea were sampled from the collection of the Mt Anann Botanic Garden, NSW. RAPD and ISSR assays generated a total of 401 RAPD and 280 ISSR fragments. High frequencies of polymorphisms, 99.39% for RAPD and 99.51% for ISSR, were detected by both markers. Three statistical approaches were employed to construct phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
26
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 21 publications
5
26
0
Order By: Relevance
“…In these studies the number of fragments ranged from 8-23 (UCB 808), 7-10 (UCB 842) and 8-24 (UCB 890). Pharmawati et al (2004) obtained fragments for the oligonucletides UCB 808 (359-1558 bp) and UCB 890 (369-1385 bp), with sizes close to those detected in this study, that ranged from 350-2000 bp. The percentage of polymorphism (90.3%) was close to that reported by Cavallari et al (2006), 89.8%, who studied populations of Ecolirium biflorum (Bromeliaceae) with RAPD markers.…”
Section: Genetic Diversitysupporting
confidence: 84%
See 1 more Smart Citation
“…In these studies the number of fragments ranged from 8-23 (UCB 808), 7-10 (UCB 842) and 8-24 (UCB 890). Pharmawati et al (2004) obtained fragments for the oligonucletides UCB 808 (359-1558 bp) and UCB 890 (369-1385 bp), with sizes close to those detected in this study, that ranged from 350-2000 bp. The percentage of polymorphism (90.3%) was close to that reported by Cavallari et al (2006), 89.8%, who studied populations of Ecolirium biflorum (Bromeliaceae) with RAPD markers.…”
Section: Genetic Diversitysupporting
confidence: 84%
“…According to Murawski & Hamrick (1990), the mean The ISSR markers used in this study therefore generated much higher values than those reported by Murawski & Hamrick (1990) for monocotyledons. The same primers used in this study generated similar results in Grevillea (Proteaceae) (Pharmawati et al, 2004) and Cycas guizhouensis (Cycadaceae) (Xiao et al 2004). In these studies the number of fragments ranged from 8-23 (UCB 808), 7-10 (UCB 842) and 8-24 (UCB 890).…”
Section: Genetic Diversitysupporting
confidence: 67%
“…The technique is rapid, simple, inexpensive and more reproducible than RAPD [23]. ISSR used to study the genetic diversity of plants for examples; Nepeta [24], thyme [25] , Mentha aquatica L. [26], satureja [27], Salvia [28], Dracocephalum thymiflorum L. [29] and Thymus [30].…”
Section: Introductionmentioning
confidence: 99%
“…Both RAPD and IS-SR marker, based on PCR techniques have proven to be a reliable, easy to generate, inexpensive and versatile set of marker that rely on repeatable amplification of DNA se-quence using single primers. The RAPD and ISSR markers can be used in the study of the genetic variability of species or natural populations and in the identification of genotypes [7][8][9][10][11][12][13][14]. In this communication, we report the feasibility of PCR-based DNA (RAPD and ISSR) marker for phylogeny study and identification for conservation of Phyllanthus species.…”
Section: Introductionmentioning
confidence: 99%